The Last Decade Publications on Diabetic Peripheral Neuropathic Pain: A Bibliometric Analysis - Du, Shu-Hao; Zheng, Yi-Li; Zhang, Yong-Hui; Wang, Ming-Wen; Wang, Xue-Qiang (Frontiers in Molecular Neuroscience, 2022)
Background: Diabetic peripheral neuropathic pain (DPNP) is a usual complication of diabetes with a high incidence and mortality. Many related studies in the field of diabetes have been published in various journals. However, bibliometrics and visual analyses in the domain of DPNP research are still lacking. The study aimed to offer a visual method to observe the systematic overview of global research in this field from 2011 to 2021. Methods: The publications from the Science Citation Index Expanded in Web of Science (WOS) in the past 11 years (from 2011 to 2021) were collected and sorted out, and those related to DPNP were extracted and analyzed. The article language was limited in English. Then, CiteSpace V was used for the bibliometric analysis of the extracted literature. Results: A total of 1422 articles met the inclusion criteria. A continuous but unstable growth in the amounts of papers published on DPNP was observed over the last 11 years. The subject sort of the 1422 papers mainly concentrates on Endocrinology Metabolism, Clinical neurology and Neurosciences from the WOS. According to the research contribution in the field of DPNP, the United States occupies a leading position, with the highest amounts of publications, citations, open access, and the H- index. Conclusion: This study provides a visual analysis method for the trend of DPNP, and offers some hidden serviceable information that may define new directions for future research.